THE ROLE OF SMART SPORTS MANAGEMENT IN PROMOTING SPORTS MARKETING THROUGH VIRTUAL MEDIA IN DIWANIYAH GOVERNORATE (Proximus Journal of Sports Science and Physical Education, 2025)
This study provides a comprehensive analysis of the role of smart sports management in enhancing sports marketing through virtual media in DIwaniyah Governorate. The research focused on investing in modern technologies to improve club performance and increase audience interaction with sports content. The study relied on an integrated methodology that combined questionnaires and semi-structured interviews to include a diverse sample of administrators, athletes, fans, media professionals, and sports management experts in the research community, with a total of (200) participants. Collecting qualitative and quantitative data helped reveal the reality of digital marketing in the governorate and identify the most prominent challenges facing it